A study of Pagu proverbs: Saving an endangered language of North Halmahera - Perangin-Angin, Dalan M.; Dewi, Novita (Indonesian Journal of Applied Linguistics, 2020)
Pagu is an endangered  Non-Austronesian  language spoken  in North Halmahera, Indonesia. This research is an endeavor to save the language specifically through documenting and studying its proverbs in order to reveal the linguistic patterns and meanings of these proverbs. A mixed qualitative and quantitative method is applied to see their structure and characteristics (Angouri, 2010; Rasinger, 2010). It presents a number of stylistic and structural features of Pagu proverbs based on the preliminary research of 2012-2014 (D. Perangin-Angin, 2013) and recent online communication with one of the Pagu  community leaders. The findings show that, first, metaphor and simile are the most common features in Pagu proverbs that function to express politeness through indirectness (Brown Levinson, 1987; Thomas, 2014). Second, structurally it was found out that Pagu proverbs do not follow the typical Europeans structure such as relationships between elements (Dundes, 1975), number of clause, types of sentences (Mac Coinnigh, 2015), and types of figurative languages (e.g. Eaglestone, 2000). But rather, Pagu proverbs vary in different structures that intend to express the Pagu culture and thought namely indirect politeness.